HYPNOSIS (HYPNOTHERAPY) IN PATIENTS UNDERGOING OPERATION: INTEGRATIVE LITERATURE REVIEW - Mohamad Judha; Josephine D. Lorica (The Malaysian Journal of Nursing (MJN), 2022)
Background: Patients undergoing operation will feel anxiety, this anxiety will affect the physiological status of the patient which can further have an impact on changes in the patient’s hemodinamic and clinical status. Fear of the process that will be undertaken, imagining the pain that will be suffered and the existence of other factors, namely the lack of support for the preparation of surgery from family and people around is like a burden for the patient. Purpose: To craft existing hypnotherapy to improve the patient’s readiness for surgery, anxiety/ worries and pain. Methods: Literature search from CIAHL, Scopus, PubMed, International Anesthesia Research Society (IARS), and Google Scholar 2002-2020, on this topic using hypnotherapy in preoperative preparation as keyword showed 8 related articles by other researchers. Results: From the results of literature studies it was found that there are several benefits of giving hypnosis before surgery. Hypnosis can also be termed as giving hypnotherapy. The impact is in the form of positive changes. There are various advantages of applying hypnosis to pre-operative patients in several countries such as France, Indonesia and America, including, reducing pain, reducing anxiety among patients to be undergoing surgery, preparing patients for surgery and reducing other post-operative impacts. Conclusion: Hypnosis can be applied in the cases of advanced preoperative patients, which can improve self-preparedness and can even decrease postoperative pain.